The Impact of Gut Microbiota on Disorders of gut-brain Interaction in Children: a Systematic Review - Parjanen, Nea (My University, 2026)
Disorders of gut-brain interaction, also known as functional gastrointestinal disorders, are common in children, but the pathophysiology is still partly unknown.These disorders affect 10-15% of children. The symptoms are typically abdominal pain, constipation, and diarrhea that occur weekly. There is clear data connecting adults' functional gastrointestinal symptoms and the composition of their gut microbiome. However, evidence in children remains limited. This study is a systematic review, where current knowledge is gathered. The data search was done in May 2024 in PubMed -database. Studies where the subjects were 1-18 years old, had a diagnosis on functional gastrointestinal disorders and their gut microbiome was analyzed, were chosen to be part of this study. Exclusion criteria included animal studies, studies of children under 1 year of age, studies focusing on individual bacterial species, and review articles. Seven articles were chosen. The results in the chosen studies varied widely. Two studies found a connection between the symptoms and a smaller alfa-diversity of microbiota. Three studies found a difference in beta-diversity between the groups. Findings regarding individual bacterial species varied considerably, making it difficult to draw definitive conclusions. This is due to the vast diversity of gut microbiota. A few studies also found preliminary results about symptomatic children having a less dynamic microbiome than healthy controls. As a conclusion, the association between children´s gastrointestinal symptoms and gut microbiome is possible, but not definitive because of the inconsistent results. Further research is needed, particularly longitudinal studies and standardized research methods, to allow for more meaningful comparisons in future studies.